A Versatile Solid Photosensitizer: Periodic Mesoporous Organosilicas with Ruthenium Tris(bipyridine) Complexes Embedded in the Pore Walls. (23rd May 2016) - Takeda, Hiroyuki; Ohashi, Masataka; Goto, Yasutomo; Ohsuna, Tetsu; Tani, Takao; Inagaki, Shinji
Abstract : Here, the synthesis of periodic mesoporous organosilicas (PMOs) containing large amounts of ruthenium(II) (Ru) tris(bipyridine) complexes within the pore walls as a solid photosensitizer is reported. The PMOs containing Ru complexes (Ru‐PMOs) are synthesized from highly purified Ru complex precursors with three attached alkylsilatrane groups in the presence of a nonionic surfactant (triblock copolymer) using polyacrylic acid as a promoter. The Ru‐PMOs show strong absorption in the visible light region up to 600 nm due to a metal–ligand charge transfer band, and redox behaviour at ≈0.8 V versus Ag/AgNO3 due to one‐electron oxidation, that are very similar to those of homogeneous Ru(dmb)3 (PF6 )2 (dmb = 4, 4′‐dimethyl‐2, 2′‐bipyridine) solution, despite the fact that the Ru complexes are embedded in the pore walls at high density. Ru‐PMOs loaded with platinum metal or iridium oxide provide efficient photocatalysis for hydrogen evolution or water oxidation, respectively, under irradiation with visible light up to 600 nm in the presence of sacrificial agents. These results indicate that Ru‐PMO is a versatile solid photosensitizer for the construction of various heterogeneous photocatalytic systems simply by placing catalytic materials in the stable mesochannels. Abstract : Periodic mesoporous organosilicas (PMOs) containing large amounts of ruthenium(II) (Ru) tris(bipyridine) complexes within the pore walls are synthesized as a solid photosensitizer. Ru‐PMOs loaded with platinum metal or iridium oxide provide efficient photocatalysis for hydrogen evolution or water oxidation, respectively, under irradiation with visible light up to 600 nm in the presence of sacrificial agents.